The Influence of Experiental Learning Model Assisted Experiment on Material Electrolyte and Non-electrolyte Solutions toward the Learning Outcome of Students Class X MIA at SMA Negeri 3 Palu - Yonathan Banua; Sri M. Sabang; Vanny M. A. Tiwow (Universitas Tadulako, 2020)
This research focused on the influence of the experiential Learning Model Assisted Experiment on material electrolyte and non-electrolyte solutions toward the learning result of science students class X MIA at SMA Negeri 3 Palu. This research used quasi-experimental with a control group research design using pre-test and post-test. The population was all of science students class X MIA at SMA Negeri 3 Palu registered in the 2016-2017 academic year. The purposive sampling was used in choosing the sample. The sample in this research was the students of experiment class (n = 32) and control class (n = 32). The statistic data used a one-party t-test with a prerequisite test: normality and homogeneity test. Based on the result of hypothesis testing, it showed that tcounted > t1-α (tcounted = 3.35 and ttable = 1.67) with the level of significance a = 0.05 and degree of freedom 61, as the result H0 was rejected and H1 was accepted, means there was a significant difference between experimental group and control group. Therefore it can be concluded that there was an influence of experiential learning model-assisted experiments on material electrolyte and nonelectrolyte solutions toward the learning result of chemistry students X MIA at SMA Negeri 3 Palu.